PENGARUH PROGRESSIVE MUSCLE RELAXATION (PMR) DIKOMBINASI MUSIK TERHADAP PENURUNAN KADAR GLUKOSA DARAH (KGD) PADA PASIEN DIABETES MELITUS TIPE 2 - Ritonga, Sukhri Herianto; Kesumawaty, Eka Putri; Nainggolan, Martua (Universitas Aufa Royhan, 2016)
Diabetes mellitus is a serious health problem in developed countries as well as in developing countries such as in Indonesia because of the incidence is increasing speedly. The purpose of this study is to know the effect of pprogressive muscle relaxationcombined by music to decrease blood glucose levels in patients on the 2 type diabetes mellitus. This study uses a quasi-experimental design with pre and post test with control group, each group consisted of 25 respondetns in Padangsidimpuan city. Statistical test used by Wilcoxon and Mann-whitney. The result of this test showed that there is a positive effect to decrease blood glucose levels significantly after PMR combined music (p<0,0001). The results of study can be input for nurse to make PMR as one of the independent nursing interventions and incorporate progressive nuscle relaxation (PMR) combined music in the management of patients with diabetes mellitus type 2.